Financial constraints and productivity: evidence from euro area companies - Annalisa Ferrando; Alessandro Ruggieri (European Central Bank (ECB), 2015)
In this paper we consider the relation between firms' financial structure, access to external finance and labor productivity using a large dataset of firm-level data for Euro-area countries during the period 1995-2011. Our empirical strategy is twofold. First we develop an indicator of financial constraints at firm level using a classification based on specific firm characteristics and various measures of financial pressure and liquidity. Second we apply this indicator to a firm-level production equation to assess the direct impact of access to finance to firm-level productivity. We estimate the impact of financial constraints on a measure of labor productivity and we find significant and negative effects in the majority of sectors across countries. The impact appears to be significantly higher in sectors like Energy, Gas and Water Supply and R&D, Communication and Information, for small and micro firms, while it is slightly smaller for firms with positive investment rates. From a cross-country perspective, while Germany and Netherlands are the least one, Italy, France, Spain and Portugal are the most affected by financial constraints, with an estimated loss of around 10% of their average real value added due to limited access to finance.
Keywords: D24; G32; O16; 330; cross-country; financial constraints; productivity; sectoral analysis; SMEs